Development of altruism in early childhood - Engin, Pınar. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
The aim of the present study was to observe development of altruism in early childhood. To gain a deeper understanding of young children’s altruism, this study questioned whether a) young children are capable of displaying altruistic behaviors, b) altruistic behaviors increase with age in early years of life, and c) altruism is a multidimensional phenomenon comprising different types of altruistic behaviors. One hundred and seventy-eight preschoolers participated in the study. Altruistic behaviors of children at the ages of 3, 4, and 5 were studied crosssectionally with a structured observational altruism task. Each child was observed in terms of helping, sharing and donation behaviors while interacting with a same-sex and same-age peer in an experimental setting. The results indicated that even children as young as 3 years of age are capable of displaying altruistic acts. Many preschool children exhibited different types of altruistic behavior. The number of children who behaved altruistically increased with age, but this relationship was valid mostly for girls. Transition from age 3 to age 4 was identified as a critical period for the development of altruism. While helping and donation behaviors were found to be more alike and to follow similar developmental pathways, sharing behavior differed from them with regard to frequency, as well as its earlier onset and its relation with age. Finally, the present study introduced an age-appropriate, structured observational task to study altruism with young children.|Keywords: altruism, altruistic behavior, helping, sharing, donation, development.
Keywords: Altruism in children.; Helping behavior in children.